Using Student-Generated Artwork as a Form of Social Studies Assessment - Zink, Danica (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
Making visual artwork like paintings, photographs, and prints can act as a valuable assessment tool in the social studies classroom. Secondary social studies educators can implement art creation to assess students throughout the learning process, in both formative and summative assessments. Art creation has unique benefits, and it can be a supplement or replacement to traditional written assessments. It offers opportunities for differentiated instruction, where students interact with the material in different ways. Art also gives an outlet for students to make new connections without the use of text. Educators can also design and implement art-based assessment as an authentic form of assessment in a visual world. Social studies teachers should implement art as an assessment tool at the secondary level.